PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN MATEMATIKA REALISTIK - Dewi Wahyuni; Rubhan Masykur; Dona Dinda Pratiwi (Universitas Muhammadiyah Metro, 2019)
Multimedia is a combination of several media. The media used is Macromedia Flash and Sparkol Videoscribe. The purpose of this study was to determine the feasibility, attractiveness and effectiveness of the use of multimedia learning with the realistic mathematical approach of class VIII MTsN 2 Bandar Lampung. The development procedure used is the Borg and Gall design development model that has been cited by Sutopo into 7 stages, namely Potential and problems, Data collection, Product Design, Design Validation, Design Revision, Product Trial, and Product Revision. The results of the material expert research and media experts obtained a "Valid" criterion with an average value of 3.4 experts and a media expert of 3.3. Then the responses of students get the criteria of "Very Interesting" with an average score of 3.33, while effectiveness gets an average of 0.71 and is included in the high category.